2022
DOI: 10.1101/2022.12.09.519601
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Positions of pivot points in quadrupedal locomotion: limbs and trunk global control in four different dog breeds

Abstract: Dogs (Canis familiaris) prefer the walk at lower speeds and the more economical trot at speeds ranging from 0.5 Fr up to 3 Fr. Important works were carried out to understand these gaits at the levels of center of mass, joint mechanics, and muscular control. However, less is known about the global control goals for limbs and overall locomotion, and of whether these global control goals are gait or breed specific. For walk and trot, we analyzed dog global dynamics based on motion capture and single leg kinetic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 65 publications
0
1
0
Order By: Relevance
“…Analogous to the VPP model, an intersection point of the GRFs above the CoM could also be found in various experimental studies for human walking [ 5 , 10 14 ], and even for some animals such as dogs [ 5 , 15 ], macaques [ 16 ] and quails [ 17 ]. In those experiments, the GRFs point to the VPP with a small spread.…”
Section: Introductionmentioning
confidence: 78%
“…Analogous to the VPP model, an intersection point of the GRFs above the CoM could also be found in various experimental studies for human walking [ 5 , 10 14 ], and even for some animals such as dogs [ 5 , 15 ], macaques [ 16 ] and quails [ 17 ]. In those experiments, the GRFs point to the VPP with a small spread.…”
Section: Introductionmentioning
confidence: 78%
“…Skipping may represent a preferred motor pattern for the bipedal macaques. Recent findings indicate that quadrupeds walk and trot with VPPs above the hip and the scapula (Andrada et al, 2023). It remains thus intriguing, if the differences in VPP heights depicted here between trailing and leading limbs holds for quadrupedal gallop, or they represent an adaptation to bipedal skipping.…”
Section: Comparison Of Skipping In Human and Macaquementioning
confidence: 82%
“…This point is called virtual pivot point (VPP) [1]. Until now, in experimental studies a VPP could always be observed: for human walking [1][2][3], human running [4], and even in animals like dogs [1,5], macaques [6], and quails [7].…”
Section: Introductionmentioning
confidence: 99%